Combinatorial Evolution of a Terpene Synthase Gene Cluster Explains Terpene Variations in Oryza . Issue 1 (11th November 2019) - Chen, Hao; Köllner, Tobias G.; Li, Guanglin; Wei, Guo; Chen, Xinlu; Zeng, Dali; Qian, Qian; Chen, Feng
Abstract : A terpene synthase gene cluster in Oryza has undergone dynamic evolution through a combination of mechanisms that underlie the diversity of volatile terpenes made by individual species. Abstract: Terpenes are specialized metabolites ubiquitously produced by plants via the action of terpene synthases (TPSs). There are enormous variations in the types and amounts of terpenes produced by individual species. To understand the mechanisms responsible for such vast diversity, here we investigated the origin and evolution of a cluster of tandemly arrayed TPS genes in Oryza . In the Oryza species analyzed, TPS genes occur as a three- TPS cluster, a two- TPS cluster, and a single TPS gene in five, one, and one species, respectively. Phylogenetic analysis revealed the origins of the two- TPS and three- TPS clusters and the role of species-specific losses of TPS genes. Within the three- TPS clusters, one orthologous group exhibited conserved catalytic activities. The other two groups, both of which contained pseudogenes and/or nonfunctional genes, exhibited distinct profiles of terpene products. Sequence and structural analyses combined with functional validation identified several amino acids in the active site that are critical for catalytic activity divergence of the three orthologous groups. In the five Oryza species containing the three- TPS cluster, their functional TPS genes showed both conserved and species-specific expression patterns in insect-damaged and untreated plants. Emission patterns of volatile terpenes from each species were largely consistent with the expression of their respective TPS genes and the catalytic activities of the encoded enzymes. This study indicates the importance of combinatorial evolution of TPS genes in determining terpene variations among individual species, which includes gene duplication, retention/loss/degradation of duplicated genes, varying selection pressure, retention/divergence in catalytic activities, and divergence in expression regulation.